The reliability of `Learning Environment Preferences` inventory in the Malaysian context - Alis, Norzaliza; Wan Jaafar, Wan Marzuki; Mohd. Ayub, Ahmad Fauzi (Scientific Research Publishing, 2015)
The study aims to determine the reliability of the Lear ning Environment Preferences (LEP) inventory among counselor trainees. A total of 100 subjects consisting of final-year students from the Guidance and Counseling Program in local universities, participated in this study. Results from the study found a high validity value of .948 for all the inventory items. The results also showed high reliability for the entire sub-scale items, achieving Cronbach’s Alpha values of .755 to .889. Based on these results, the LEP is considered appropriate to be used in order to test counselor trainees’ cognitive complexity.